Women in German Expressionism Gender, Sexuality, Activism - Finger, Anke; Shoults, Julie (Social History, Popular Culture, And Politics In Germany, 2023)
This collection, for the first time, explores women's self-conceptions and representations of women's and gender roles in society in their own Expressionist works. How did women approach themes commonly considered to be characteristic of the Expressionist movement, and did they address other themes or aesthetics and styles not currently represented in the canon? Women in German Expressionism centers its analysis on gender, together with difference, ethnicity, intersectionality, and identity, to approach artworks and texts in more nuanced ways, engaging solidly established theoretical and sociohistorical approaches that enhance and update our understanding of the material under investigation. It moves beyond the masculine, "New Man," viewpoint so firmly associated with German Expressionism and examines alternative, critical, and divergent interpretations of the changing world at the time. This collection seeks to broaden the theorization, scholarship, and reception of German Expressionism by-much belatedly-including works by women, and by shifting or redefining firmly established concepts and topics carrying only the imprint of male authors and artists to this day.